(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the BMI status of first year medical students. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the This study was conducted at Al-Tibri Medical College & Hospital, Isra University campus, Karachi, from July 2019 to December 2019. Materials and Methods: All 89 students enrolled in first year MBBS class were involved in the study. Data was evaluated using SPSS version 25. Results: Mean age of students was 19.64. Females were n=50 (56.2%) and males were n=39 (43.8%). The mean Body Mass Index was 21.98. First year male medical students overweight and obese are n=17 (43.6%). Female medical students overweight and obese are n=15 (30%). The overall daily physical activity done by the students is n=60 (67.4%). Conclusion: Study reveals majority of first year medical students falls into the category of having normal BMI and female students are more physically active in their daily chores.